Coaching for person-centered healthcare : a solution-focused approach to collaborative care - Cook, Elaine (Certified solution-focused coach); Greene, Gilbert J.; Maxwell, Joanne (Abingdon, Oxon ; New York, NY : Routledge, 2025)
This guide introduces a humanistic, solution-focused coaching model, using lived experience to demonstrate how profound changes in our healthcare experiences and system, for patients and staff, are possible; while also supporting readers to develop their own coaching skills. Combining research, theory, and practice shared through personal experience, readers are introduced to solution-focused, dialogic tools for use in promoting person-centred care. The first section of the book introduces the coaching model and explores its theoretical and philosophical underpinnings, drawing on theories from neuroscience, neurobiology, communication sciences, humanistic psychology, and positive psychology. The second section of the book transitions from theory and research into clinical practice, making evident the broad range of healthcare contexts and domains in which the humanistic, solution-focused approaches are implemented, as well as the profound personal and professional implications associated with their use. The third section of the book focuses on the lived experience of four people, focusing on their interactions with healthcare before and after their coaching training, emphasizing the difference a humanistic, solution-focused approach has made for them and their families. The final section then turns to organizational change and explores how solution-focused coaching provides insights, perspectives, and aspirations for system change. This engaging text is ideal reading for healthcare professionals, teachers, and leaders looking to develop and improve the care they deliver, the experiences of the people they are working with, and the organizations they deliver it within.
Healing Healthcare : How Coaching Leads to Optimal Functioning For Clients and Staff / Elaine Cook, PhD -- A Humanistic, Solution-Focused Approach to Person-Centered Care and Client-Activation / Gilbert J. Greene, PhD, LISW -- The Influence of a Humanistic, Solution-focused Approach on Healthcare Research / Laura R. Bowman, PhD, OT Reg. (Ont.) -- How Solution Focused Conversations Changed My Practice : A reflection on the Synergy of Bioethics Consults and a Solution-Focused Approach / Dolly Menna-Dack, MHSc -- A Solution-Focused Approach for Health Care Providers Supporting Autistic Children & Youth / Moira Peña OT Reg. (Ont.) -- Dealing With Behaviour : Collaborative Behaviour Support / Heidi Schwellnuss, PhD., Brian Freel -- A Humanistic, Solution-Focused Approach with Older Adults / Jacqueline Carver, MSW, LISW, Gilbert J. Greene, Ph.D., LISW -- Humanistic, Solution Focused Nursing in The Pediatric Psychopharmacology Clinic : An Antidote to Burnout / Cathy Petta, RN -- Solution-focused Healthcare: Application and Benefits in Occupational Therapy / Amanda Musto, OT Reg. (Ont.) -- A Discussion Of Solution Focused Praxis Through A Lived Experience Of Disability / Wesley Magee-Saxton -- Embracing a Humanistic Solution-Focused Approach : Implications for Me Living with Cerebral Palsy (CP) and My Family / Nikky Henderson -- The Power of Compassion and Gratitude / Gunjan Seth -- Reflections and Observations as a Parent and Coach of a Child who Triumphed over Tribulation / Candace Muskat -- A Humanistic, Solution-Focused Approach : Implications for the Legal System / Anna Trbovich -- A Humanistic, Solution-Focused Approach to Meeting the Challenges in Education / Kim Weishar -- Humanistic Solution-Focused Healthcare Leadership : Fostering psychological well-being and psychological safety / Amy Hu, Sarah Keenan -- Humanistic, Solution-Focused Implementation : Organization and System Implications / Joanne Maxwell.
Keywords: Patient-centered health care; Health care teams; Medical personnel and patient; MEDICAL / Health Care Delivery; MEDICAL / Education & Training; MEDICAL / Caregiving